A retrospective study on the outcomes of yttrium-90 radiation segmentectomy with resin microspheres compared to microwave ablation for early primary hepatocellular carcinoma - Abdalla, Omar; Mcgonigle, Trey; Doyle, Patrick; Kelm, Nathaniel; Osama, Tag Alsir; Grice, Jared; Huang, Shi; Brown, Daniel B.; Case, Meaghan Dendy (Journal of Gastrointestinal Oncology, 2026)
Background: Yttrium-90 (Y-90) radiation segmentectomy (RS) has become an established method for interventional radiologists to treat hepatocellular carcinoma (HCC). Literature suggests similar tumor response and overall survival (OS) rates between Y-90 RS using glass microspheres and percutaneous microwave ablation (MWA) in early-stage HCC, with a potential improvement in progression-free survival (PFS) for Y-90 RS. However, the literature does not address the use of Y-90 RS with resin microspheres when compared to MWA. The aim of this study is to evaluate the efficacy of Y-90 RS with resin microspheres vs. percutaneous MWA in patients with American Joint Committee on Cancer (AJCC) stage 1 solitary tumor HCC ≤4 cm.Methods: From 2016 to 2024, 60 patients were included in this retrospective study (20 RS and 40 MWA). Wilcoxon rank sum and Pearson’s χ2 or Fisher’s exact tests were used to evaluate differences in baseline demographics and clinical characteristics between groups. Tumor response was assessed using modified Response Evaluation Criteria in Solid Tumors (mRECIST) 1.1 and compared between the two treatment groups with a chi-squared test. Differences in survival outcomes were assessed using Kaplan-Meier and Cox regression models for both OS and PFS.Results: In the overall study population, both groups had similar baseline characteristics except for greater tumor diameter in the RS group (P0.99). Both Kaplan-Meier plots and Cox regression did not find significant differences in PFS and OS between MWA and RS groups.Conclusions: The study suggests Y-90 RS with resin achieves similar tumor response, PFS, and OS compared to MWA in the management of AJCC stage 1 solitary tumor HCC lesions ≤4 cm. These findings were demonstrated despite the RS cohort having a larger tumor diameter.